Black Love, Black Hate - Felice (The Ohio State University Press, 2018)
Felice D. Blake's Black Love, Black Hate: Intimate Antagonisms in African American Literature highlights the pervasive representations of intraracial deceptions, cruelties, and contempt in Black literature. Literary criticism has tended to focus on Black solidarity and the ways that a racially linked fate has compelled Black people to counter notions of Black inferiority with unified notions of community driven by political commitments to creative rehumanization and collective affirmation. Blake shows how fictional depictions of intraracial conflict perform necessary work within the Black community, raising questions about why racial unity is so often established from the top down and how loyalty to Blackness can be manipulated to reinforce deleterious forms of subordination to oppressive gender, sexual, and class norms.